Low serum albumin concentrations are associated with disease severity in patients with myasthenia gravis. Issue 39 (September 2016) - Weng, Yi-Yun; Yang, De-Hao; Qian, Mei-Zi; Wei, Mao-Mao; Yin, Fang; Li, Jia; Li, Xiang; Chen, Ying; Ding, Zhang-Na; He, Yi-Bo; Zhang, Xu
Abstract : Abstract: Serum albumin (S-Alb) is a widely used biomarker of nutritional status and disease severity in patients with autoimmune diseases. We investigated the correlation between S-Alb and the severity of myasthenia gravis (MG). A total number of 166 subjects were recruited in the study. Subjects were divided into 3 groups (T1 to T3) by S-Alb levels: T1: 21.1 to 38.4 g/L, T2: 38.5 to 41.5 g/L, T3: 41.6 to 48.9 g/L. Regression analysis was performed to determine the correlation of initial albumin concentrations and the severity of disease of MG. Lower levels of S-Alb were observed in subjects with increased disease severity than those with slight disease severity, meanwhile, incidence of myasthenia crisis increased in the lower albumin tertiles ( P < 0.001). The disease severity assessment was performed according to the criteria established by the Myasthenia Gravis Foundation of America. After adjusting for age, sex, body mass index (BMI), and duration of disease, it showed that higher S-Alb concentrations were associated with lower disease severity. Odds ratios (ORs) of T2 to T3 were 0.241 (95% CI: 0.103–0.566, P < 0.001), 0.140 (95% CI: 0.054–0.367, P < 0.001) when compared with subjects in the T1, respectively. When subjects were stratified into hypoalbuminemia and normal albumin groups, we found that the association between S-Alb and MG remained significant in the hypoalbuminemia group only (OR: 0.693, 95% CI: 0.550–0.874, P = 0.002) after further adjustment for age, sex, BMI, and duration of disease. This is the first study to demonstrate that S-Alb was independently associated with MG severity. In patients with low S-Alb, S-Alb concentration could be a potential biomarker for MG disability.